GAMBARAN PARTUS LAMA DENGAN KEJADIAN ASFIKSIA NEONATORUM PADA BAYI BARU LAHIR DI RUANG BERSALIN RSUD ENDE - Marieta K S Bai (Poltekkes Kemenkes Kupang, 2022)
Asphyxia is a condition where a baby can not breathe spontaneously immediately and regularly after birth (Saifudin, 2006). Neonatorum asphyxia mortality rate in 2008 is 19, while the morbidity rate of asphyxia due to long deliveries in January-October 2015 there were 22 cases. The purpose of this research is to know the description of long deliveries with the incidence of asphyxia neonatorum in newborn infants in hospital maternity room Ende. This research uses the documentation study population was taken from mothers who have long obstructed labour and gave birth to babies who experience asphyxia January-October 2015 period were 22 people total sampling method or the total population. Data collection tool using data collection sheets. Results showed that respondents had long obstructed labour due to HIS disorder with the incidence of asphyxia were 9 people and gave birth to infants with mild asphyxia at 66.7%, asphyxia was 33.3% and severe asphyxia did not exist. In respondents who had long obstructed labour due to abnormality of the birth canal as many as 10 people gave birth to infants with mild asphyxia 50%, asphyxia 20% and 30% severe asphyxia. Respondents who had long obstructed labour due to fetal abnormalities as many as 3 people and all respondents gave birth to infants with asphyxia being. The research concludes that all the respondents who gave birth as long as obstructed labour had a baby with asphyxia. Suggestions for educational institutions to continue providing materials to students in particular concerning long obstructed labour and neonatal asphyxia and for RSUD Ende to continue and to provide information about the safe delivery for the mother.